The Influence of Inclusion and Guided Discovery Teaching Style on Learning Results of Bottom Passing Volyball - Tedi Tariki; Anggi Setia Lengkana; Yudha Munajat Saputra (JUARA : Jurnal Olahraga, 2023)
This study aimed to examine the effect of inclusive teaching styles and guided discovery on learning outcomes of underhand passing in volleyball. The research method uses experimental research methods with a pretest-posttest control group design. The sample in this study was 40 students of SDN Leuwiliang. The research instrument used an observation sheet for the basic skills of passing down in volleyball. Data analysis using SPSS v.20 using paired sample t-test and independent sample t-test. This study concluded that there is an influence of inclusive teaching style. It guided discovery on the underhand passing, and there is a difference in the effect of inclusive teaching style and driven discovery teaching style on the volleyball bottom passing learning outcomes. The guided discovery teaching style shows more significant learning outcomes in volleyball underpass.